Optimization of process parameters for cellulose nanocrystals derivative from coconut shell - Dennis O. Bichang’a; Isiaka O. Oladele (Next Materials)
In the present study, optimization of process parameters for cellulose nanocrystals (CNCs) derived from coconut shell was carried out. The cellulose nanocrystals were extracted from coconut shell via an acid hydrolysis method. The collected coconut shells were prepared and purified using dewaxing, alkali, and bleaching pretreatment processes. The study used Design Expert 13 software (Stat-Ease Inc., USA) to design the experiments. A two-level factorial design based on Face-centred central composite design (FCCD) of the response surface methodology (RSM) was used to validate an empirical model. The main and interactive effects of the independent variables, sulphuric acid concentration, hydrolysis temperature, and reaction time, were investigated using the response methodology approach. The obtained regression model was used to optimize the yield of CNC. The extracted nanocellulose were characterized in terms of its surface morphology and chemistry, and crystallinity using scanning and transmission electron microscopes (SEM/TEM), Fourier Transform Infrared (FT-IR) spectroscopy, Thermogravimetric analysis (TGA), and X–Ray diffraction (XRD) analysis. The SEM image of the extracted CNCs revealed an irregular morphology with no surface impurities. The extracted CNCs had a spherical-shaped structure with an average particle size of 54.91 nm, which is within the nanoscale dimensions (1–100 nm). CNCs reported a higher crystallinity of 90.41 % compared to 80.29% for the chemically purified cellulose (CPC). An optimum yield of 82.47 % CNCs was obtained at 55.00 wt% sulphuric acid concentration, 45.00°C hydrolysis temperature, and 45.00 min reaction time. These optimized conditions were validated to confirm the precision. Hence, the extracted CNCs can be suitably used as reinforcing fillers in the fabrication of bio-nanocomposites for diverse engineering applications.